Semiotic Discourse of the Socio-Political Sphere of the Modern Russian Society: Challenges of Multimodality - Babaitsev, Andrei V.; Voskoboynikov, Sergey G.; Schukina, Tatyana V.; Topchiy, Inna V. (International Journal of Criminology and Sociology, 2022)
The article discusses the semiotic discourse of the socio-political sphere of modern Russian society. The modern challenges of multimodality of the socio-political sphere of modern Russian society are analyzed, taking into account the interdisciplinarity of meaningful sign and symbolic constructions. The semiotic discourse of the socio-political sphere is a certain type of interdisciplinary analytical research of socio-political communication aimed at interpreting the process of creating semantic meaning as social and political practice. Multi- in the term “multimodality” implies the fact that there are a number of modes available for reproduction by all members of a social or political community. The semiotic approach to the socio-political sphere of Russian society is utilized to accomplish this study. Furthermore, Studies of the concept of discourse, as well as the specifics of the use of this concept and the development of discourse analysis as a method in the socio-political scientific field, are taken into account to achieve the purpose of the study.